2001
DOI: 10.1016/s1388-2457(01)00636-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic source localization of auditory evoked fields and intracerebral evoked potentials: a comparison of data in the same patients

Abstract: The results suggest that both techniques are useful and may be used together in a complementary fashion. Intracerebral recordings allow the researcher to validate and interpret surface recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
194
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(216 citation statements)
references
References 28 publications
21
194
1
Order By: Relevance
“…The primary auditory cortex, the lateral aspects of which are assumed to harbor the P50 generator (Godey, 2001), is not directly accessible with the subdural and intrahippocampal depth electrodes used in the present study. Hence, the lateral temporal strip and grid electrodes may represent components originally generated in Heschl's gyrus.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary auditory cortex, the lateral aspects of which are assumed to harbor the P50 generator (Godey, 2001), is not directly accessible with the subdural and intrahippocampal depth electrodes used in the present study. Hence, the lateral temporal strip and grid electrodes may represent components originally generated in Heschl's gyrus.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Hence, the lateral temporal strip and grid electrodes may represent components originally generated in Heschl's gyrus. Unfortunately, there are as yet no invasive gating studies in patients with temporal depth electrodes inserted along a lateral-medial axis, although the P50 component as such has been investigated by such an approach (Godey, 2001). …”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In normal adults, the neuroanatomical source of the M100 component is further anterior in the right hemisphere (Baumann et al, 1991). We and others have previously shown that patients with schizophrenia demonstrate disturbed inter-hemispheric asymmetry of the M100 generator location , Reite et al, 1989, Rockstroh et al, 2001, Tiihonen et al, 1998.The M100 component appears to be generated by lateral aspects of the transverse gyrus of Heschl and the planum temporale of the superior temporal gyrus (Godey et al, 2001, Reite et al, 1994. Abnormal planum temporale asymmetry has also been implicated as disturbed in schizophrenia (e.g., Shapleske et al, 1999 for a review).…”
mentioning
confidence: 86%